The stimulating effect of ghrelin on gastric motility and firing activity of gastric‐distension‐sensitive hippocampal neurons and its underlying regulation by the hypothalamus. Issue 1 (30th October 2013) - Xu, Luo; Gong, Yanling; Wang, Hongbo; Sun, Xiangrong; Guo, Feifei; Gao, Shengli; Gu, Fang
New Findings What is the central question of this study? Is there a direct pathway of ghrelin from the hypothalamic arcuate nucleus to the hippocampus? Is this pathway involved in the regulation of gastric motility and gastric afferent signalling? What is the main finding and its importance? There exists a direct pathway of ghrelin from the hypothalamic arcuate nucleus to the hippocampus that is involved in the regulation of gastric motility. In the emotional hub hippocampus, ghrelin is involved in the regulation of gastric motility and gastric afferent signalling. These effects can be regulated by the hypothalamic arcuate nucleus. This supports and advances the theory of energy balance involving the regulation of the central and brain–gut peptides. Ghrelin is an acylated peptide originally identified in the rat stomach as the endogenous ligand for growth hormone secretagogue receptor (GHSR) that promotes gastric motility. Our aims were to explore the effects of ghrelin on gastric‐distension‐sensitive neurons in the hippocampus and the potential for ghrelin to regulate gastric motility through the arcuate nucleus (Arc). Single‐unit discharges in the hippocampus were recorded extracellularly, and gastric motility in conscious rats was monitored. The expression of GHSR‐1a in the hippocampus was determined by PCR, Western blot and fluo‐immunohistochemistry staining. Retrograde tracing and fluo‐immunohistochemistry staining were used to determine ghrelin neuron projection. Ghrelin–Fluoro‐Gold double‐labelled neurons and GHSR‐1a expression were observed in the Arc and hippocampus, respectively. There were gastric‐distension‐sensitive neurons in the hippocampus that could be excited by ghrelin or by electrical stimulation of the Arc. The excitatory effects could be blocked completely or partly by pretreatment with the ghrelin receptor antagonist [d‐Lys‐3]‐GHRP‐6. Gastric motility was significantly promoted by the administration of ghrelin into the hippocampus in a dose‐dependent manner that could be completely abolished by [d‐Lys‐3]‐GHRP‐6. Electrical stimulation of the Arc could promote gastric motility as well. Nevertheless, these effects could be mitigated by pretreatment with [d‐Lys‐3]‐GHRP‐6. Electrical lesioning of the hippocampus diminished the excitatory effects on gastric motility that were induced by electrical stimulation the Arc. Our findings suggest that ghrelin plays an important role in promoting gastric motility via the hippocampus. The Arc may be involved in regulation of the influence of the hippocampus on gastric motility.